IEEE Access Special Section Editorial: Blockchain Technology: Principles and Applications - Wenbing Zhao (IEEE Access, 2021)
Blockchain is a disruptive technology for building consensus and trust in a peer-to-peer network without centralized control. It was first used in bitcoin, the very first cryptocurrency released at the beginning of 2009, to implement a secure ledger of transactions. This secure ledger ensures that once a transaction is placed in the ledger, it cannot be altered without being detected, which is a prerequisite for any digital currency implementation because it must guarantee that no one can double-spend one’s money. The interest in blockchain exploded in recent years. The number of publications indexed by Web of Science on blockchain increased from 2 in 2013 (the first year in which publications on blockchain started to appear), to 4 in 2014, to 21 in 2015, to 118 in 2016, to 521 in 2017, to 1954 in 2018, to 3667 in 2019, and to 3945 in 2020. As of June 29, 1569 articles have been published in 2021.